A Case of Avascular Necrosis (AVN) (Advancements in Homeopathic Research, 2022)
Let us see what is Avaculer Necrosis. The Taber’s Cyclopedic Medical Dictionary defines – “Avascular necrosis (AVN) or Osteonecrosis – The death of a segment of bone, usually caused by insufficient blood flow to a region of the skeleton. This is a relatively common disorder, and an estimated 10% of total joint replacements are for osteonecrosis. From 5% to 25% of patients receiving prolonged therapy with corticosteroids will develop this condition. Treatment is symptomatic, but in some cases of osteonecrosis of the knee or hip joint prosthetic replacement is required.”
Keywords: Avascular Necrosis; (AVN); Osteonecrosis